Gender trends in education and marriage stability - Murínová, Dominika; Křečková Kroupová, Zuzana, 1972-; JACKSON, Ian; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The increasing number of women in the tertiary education starts to be a global phenomenon. This gender ratio inequality in higher education is mainly visible in industrialized countries like Australia, the Nordic countries, and the United Kingdom. Main goal of this paper is to investigate whether the increasing number of divorces and marriage stability are affecting the decision of a person whether to attend tertiary education or not. We begin with a presentation of the already existing researches in this field. Many of them are, however, looking at how divorces affect children’s performance at school, not the other way around, which will be our goal in this thesis. The second part of the paper is focusing on Sweden, which we chose as the country of our interest where much more women are attending tertiary education than men and where the number of divorces increased dramatically. In the third part we provide panel data analysis of this issue and talk about the empirical results we obtained.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses